2016
DOI: 10.1002/brb3.492
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific birth rates in women with epilepsy: a population‐based study

Abstract: ObjectiveThe aim of this study was to investigate birth rates and use of hormonal contraception in different age groups among women with epilepsy (WWE) in comparison to women without epilepsy.Materials and MethodsDemographic data and medical information on more than 25,000 pregnant women (40,000 births), representing 95% of all pregnancies in Oppland County, Norway, were registered in the Oppland Perinatal Database in the period 1989–2011. Data were analyzed with respect to epilepsy diagnoses, and 176 women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
12
1
2
Order By: Relevance
“…There has been controversy as to whether women with epilepsy (WWE) are at increased risk for infertility and impaired fecundity and whether antiepileptic drug (AED) use and AED category are factors. The majority of retrospective studies have found that WWE have lower birth rates and fewer children than women in the general population . However, a retrospective cohort study of the Icelandic population found no significant difference in incident fertility rates between WWE and women in the general population, and a prospective controlled study of 89 WWE seeking pregnancy and 108 controls in the USA found no difference in fertility rates between the two groups over the course of a 1‐year follow‐up .…”
Section: Introductionmentioning
confidence: 98%
“…There has been controversy as to whether women with epilepsy (WWE) are at increased risk for infertility and impaired fecundity and whether antiepileptic drug (AED) use and AED category are factors. The majority of retrospective studies have found that WWE have lower birth rates and fewer children than women in the general population . However, a retrospective cohort study of the Icelandic population found no significant difference in incident fertility rates between WWE and women in the general population, and a prospective controlled study of 89 WWE seeking pregnancy and 108 controls in the USA found no difference in fertility rates between the two groups over the course of a 1‐year follow‐up .…”
Section: Introductionmentioning
confidence: 98%
“…Patients with COE have lower fertility when compared to unaffected controls . Adult onset and active epilepsy have also been associated with lowered fertility in large population‐based studies . Both physical and social factors likely contribute to lowered fertility.…”
Section: Introductionmentioning
confidence: 99%
“…the epilepsy group and healthy group (women without registered chronic diseases). The validation procedure of epilepsy is described elsewhere . The frequency of epilepsy was 0.60%.…”
Section: Methodsmentioning
confidence: 99%